2006
DOI: 10.1002/bem.20265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of information and 50 Hz magnetic fields on cognitive performance and reported symptoms

Abstract: The aim of this study was to explore the role of expectancies and beliefs about the potential effects of electromagnetic fields (EMFs) (what the subject thought the effect was going to be) and the effects of 50 Hz magnetic fields (400 mT rms ) acute exposure on cognitive performance, the reporting of physical symptoms and some psychological and physiological parameters. Seventy-four healthy male volunteers aged between 40 and 60 years of age were randomly assigned to one of five groups, which differed in (1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Whether some people are particularly predisposed to experiencing a nocebo effect remains unclear. Several potential predisposing factors have been suggested including gender (Liccardi et al ., 2004), anxiety (Nevelsteen, Legros, & Crasson, 2007), somatization (Szemerszky, Koteles, Lihi, & Bardos, 2010), somatosensory amplification (Witthöft & Rubin, 2013), low optimism (Geers, Helfer, Kosbab, Weiland, & Landry, 2005), and baseline symptoms (de la Cruz, Hui, Parsons, & Bruera, 2010). However, in a systematic review, Webster, Weinman, and Rubin (2016) highlighted inconsistent findings with regard to the importance of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Whether some people are particularly predisposed to experiencing a nocebo effect remains unclear. Several potential predisposing factors have been suggested including gender (Liccardi et al ., 2004), anxiety (Nevelsteen, Legros, & Crasson, 2007), somatization (Szemerszky, Koteles, Lihi, & Bardos, 2010), somatosensory amplification (Witthöft & Rubin, 2013), low optimism (Geers, Helfer, Kosbab, Weiland, & Landry, 2005), and baseline symptoms (de la Cruz, Hui, Parsons, & Bruera, 2010). However, in a systematic review, Webster, Weinman, and Rubin (2016) highlighted inconsistent findings with regard to the importance of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…But this result has to be treated with caution, since the heterogeneity conclusion is again driven by only one study [Preece et al, 1998: D ¼ À0.92], whereas none of the later studies on working memory (number) were able to replicate such an effect: Delhez et al [2004]: D ¼ 0.14 and Nevelsteen et al [2007]: D ¼ À0.07.…”
Section: Discussionmentioning
confidence: 96%
“…b Podd et al [2002], Crasson et al [1999], Preece et al [1998], Delhez et al [2004], Whittington et al [1996], Keetley et al [2001], Nevelsteen et al [2007], Kurokawa et al [2003].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent studies using sinusoidal 50 Hz MF (at 20, 100, or 400 mT) found no effects on working memory and cognitive flexibility [Delhez et al, 2004;Nevelsteen et al, 2007], selective and sustained attention tasks [Delhez et al, 2004;Crasson and Legros, 2005;Nevelsteen et al, 2007], and reaction time or time perception [Kurokawa et al, 2003;Delhez et al, 2004;Crasson and Legros, 2005]. However, a consistent effect appears to exist when the 50 Hz exposure level is >500 mT.…”
Section: Introductionmentioning
confidence: 98%